2016
DOI: 10.1371/journal.pone.0167951
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Immunogenicity and Efficacy of Prime-Boost Vaccination with ChAd63 and MVA Encoding ME-TRAP against Plasmodium falciparum Infection in Adults in Senegal

Abstract: Malaria transmission is in decline in some parts of Africa, partly due to the scaling up of control measures. If the goal of elimination is to be achieved, additional control measures including an effective and durable vaccine will be required. Studies utilising the prime-boost approach to deliver viral vectors encoding the pre-erythrocytic antigen ME-TRAP (multiple epitope thrombospondin-related adhesion protein) have shown promising safety, immunogenicity and efficacy in sporozoite challenge studies. More re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 30 publications
2
47
0
Order By: Relevance
“…Multiple rounds of optimization returned a heterologous prime/boost protocol with chimpanzee adenovirus 63 (ChAd63) and modified vaccinia Ankara virus (MVA), respectively. A recent small phase II study with 115 participants in Senegal showed no efficacy of this vaccine, and combined analysis with earlier data from Kenia returned only a small, albeit significant, delay until patency [40].…”
Section: Feasible Leads: Testing One Antigen At a Timementioning
confidence: 90%
“…Multiple rounds of optimization returned a heterologous prime/boost protocol with chimpanzee adenovirus 63 (ChAd63) and modified vaccinia Ankara virus (MVA), respectively. A recent small phase II study with 115 participants in Senegal showed no efficacy of this vaccine, and combined analysis with earlier data from Kenia returned only a small, albeit significant, delay until patency [40].…”
Section: Feasible Leads: Testing One Antigen At a Timementioning
confidence: 90%
“…Group A (n:28): ChAd63 ME-TRAP increasing the dose from 1 × 10 8 to 5 × 10 10 vp ID (groups 1-4) and from 1 × 10 10 to 2 × 10 11 IM (groups 5-7) Group B (n:26): ChAd63 ME-TRAP, followed at 8 weeks by MVA ME-TRAP and a booster dose for 5 volunteers with ChAd63 ME-TRAP and for 6 volunteers with MVA ME-TRAP NE [116] 36 adults (18-50 years-old) Trial A (n:16): ChAd63 ME-TRAP n:6 1 × 10 10 VP Trial B (n:30): 10 5 × 10 10 VP a the 56 days MVA ME-TRAP 2 × 10 8 by intramuscular route (IM) NE [111] 138 children and infants Gambia 2-6 year-olds Group 1a (n:6): 1 × 10 10 vp ChAd63 ME-TRAP and 1 × 10 8 pfu MVA ME-TRAP Group 1b (n:6): 1 × 10 10 vp ChAd63 ME-TRAP and 2 × 10 8 pfu MVA ME-TRAP Group 1c (n:6): 1 ml HDCRV Group 1d (n:6): 5 × 0 10 vp ChAd63 ME-TRAP and 1 × 10 8 pfu MVA ME-TRAP Group 1e (n:6): 5 × 10 10 vp ChAd63 ME-TRAP and 2 × 10 8 pfu MVA ME-TRAP Group 1f (n:6): 1 ml HDCRV Gambia 5-12 month-olds Group 2a (n:12): 1 × 10 10 vp ChAd63 ME-TRAP and 1 × 10 8 pfu MVA ME-TRAP Group 2b (n:12): 5 × 10 10 vp ChAd63 ME-TRAP and 1 × 10 10 pfu MVA ME-TRAP Group 2c (n:12): No vaccine Gambia 10 week-olds Group 3a (n:12): 1 × 10 10 vp ChAd63 ME-TRAP and 1 × 10 8 pfu MVA ME-TRAP Group 3b (n:12): 5 × 10 10 vp ChAd63 ME-TRAP and 1 × 10 8 pfu MVA ME-TRAP Group 3c (n:12): No vaccine Burkina Faso (n.30) 5-17 month-olds 5 × 10 10 vp ChAd63 ME-TRAP and 1 × 10 8 pfu MVA ME-TRAP NE [110] Chad63 MVA ME-TRAP (Phase II) 120 adults (18-50 years-old) n. 120 ChAd63 ME-TRAP (5 × 10 5 vp) after 8 weeks n. 60 cases: MVA ME-TRAP (2 × 10 8 pfu) n. 60 controls: anti-rabies vaccine (0.5 ml) 8% adjusted efficacy: 50% (PCR positivity: more than 10 parasites per μl) [117] 120 adults (18-50 years-old) n. 120 ChAd63 ME-TRAP (5 × 10 5 vp) after 8 weeks n. 60 cases: MVA ME-TRAP (2 × 10 8 pfu) n. 60 controls: anti-rabies vaccine (0.5 ml) 67% (PCR positivity: more than 10 parasites per μl) [118] although CD4 + and CD8 + T-cell responses did not increase, being limited after the second and third immunization [23].…”
Section: Adultsmentioning
confidence: 99%
“…A trial involving adults in Senegal [117] to assess vaccine efficacy using a polymerase chain reaction (PCR) assay was able to detect > 10 parasites/μl blood. PCR was positive for 12 out of 57 participants vaccinated with ChAd63 ME-TRAP with a booster dose of MVA ME-TRAP and 13 out of 58 control patients who received an anti-rabies vaccine were positive by PCR, giving 8% efficacy (which was not statistically significant).…”
Section: Chad63 Mva Me-trapmentioning
confidence: 99%
See 1 more Smart Citation
“…This vector was assessed with and without an MVA booster dose, and was found to elicit strong antibody and T‐cell responses, which could be increased in magnitude and durability by an MVA boost. Another chimpanzee adenoviral vector, ChAd63, has also been evaluated in several clinical trials (malaria, leishmaniasis) with results showing excellent safety and immunogenicity, even in infants and children.…”
Section: Enhanced Adenoviral Vectorsmentioning
confidence: 99%